Pengaruh Aktivitas, Solvabilitas dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan Manufaktur Sub Sektor Makanan dan Minuman di Bursa Efek Indonesia Tahun 2012 – 2017 - Hendry Gunawan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this research is to determine the effect of the ratio of activity, solvability, firm size to company’s profitability in manufacturing companies food and beverages sub-sector listed in Indonesia Stock Exchange period 2012-2017. The sampling method is done by using purposive sampling. The method of collecting secondary data is taken from the IDX that publishes the financial statements. This research uses descriptive statistical analysis and multiple regression analysis with Eviews 9. The results showed that total asset turnover is positive significant, debt to equity ratio is not significant and firm size is not significant to profitability of company. F-test results show total asset turnover, debt equity ratio and size independent variables in this research simultaneously don’t have a significant effect on the return of equity of companies in the food and beverages sub-sector listed on the Indonesia Stock Exchange.